Contemporary trends and ethical concerns in clinical photography in Saudi Arabia: A preliminary study - Amr Jamal; Khalid M Al Ghamdi; Shabana Tharkar; Ibrahhem Al-Rabiah; Mohammed Al-Shehri; Abdulmalik Al-Sahaf; Mohammed Al-Baz; Abdullah Al-Rowailey; Abdulrahman Al-Fowzan (Wolters Kluwer Medknow Publications, 2022)
Objectives: Medical photography is imperative for maintaining documentation of patient records and aiding in diagnosis and management, research, education, and training. Smartphones have replaced conventional photography due to their ease of availability, accessibility, and storage; however, their use raises privacy and ethical concerns. The objective of the present study was to determine the current trends in clinical photography and to assess the ethical issues involved in this field. Methods: A cross-sectional survey was used to interview physicians registered at the Saudi Commission for Health Specialties. Data collection was performed using the SurveyMonkey platform, and the final sample included complete responses from 210 participants. Results: A total of 147 physicians (70%) reported taking clinical photographs. Personal smartphones were the most common device used by 116 (79%) physicians, and 43 (29.3%) reported also using hospital cameras for photographing their patients. Patient visit follow-ups and medical education/training were the most popular reasons for clinical photography. Access to these devices was not well secured, with only 42 (28.6%) physicians reporting storing them in a separate folder with a password. Furthermore, no significant differences were observed in consent-taking practices between male and female patients and in the cross-analysis between physicians' and patients' genders. However, significant differences were obtained in the method of consent for identifiable and nonidentifiable photographs, with written consent preferred over verbal in identifiable photographs (P = 0.025). Common misuses included not obtaining proper consent before taking and while sharing the photographs, which raises serious privacy concerns. Patients' refusal to be photographed was the most common barrier reported by 55 (26.2%) physicians. Conclusions: Physicians mostly resorted to personal smartphones for capturing and storing patient photographs. This study identified a widespread prevalence of inadvertent practices related to inadequate consent, photograph sharing, and unsecured storage, which increases the risk of a breach of confidentiality. There is an urgent need to enforce standard guidelines and regulations addressing patients' privacy and ethical concerns involving digital photography in clinical practice.